2015
DOI: 10.1038/onc.2015.35
|View full text |Cite
|
Sign up to set email alerts
|

Reactive oxygen species regulate Smac mimetic/TNFα-induced necroptotic signaling and cell death

Abstract: Necroptosis represents a key programmed cell death pathway involved in various physiological and pathophysiological conditions. However, the role of reactive oxygen species (ROS) in necroptotic signaling has remained unclear. In the present study, we identify ROS as critical regulators of BV6/tumor necrosis factor-α (TNFα)-induced necroptotic signaling and cell death. We show that BV6/TNFα-induced cell death depends on ROS production, as several ROS scavengers such as butylated hydroxyanisole, N-acetylcysteine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
159
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 208 publications
(164 citation statements)
references
References 53 publications
4
159
0
1
Order By: Relevance
“…Taken together, our results clearly demonstrated that there is a link among ROS, TLR4 and RIP3, and that ROS mediates the HG-induced activation of TLR4 and necroptosis. Schenk et al [31] more recently showed that ROS regulate Smac mimetic/TNF-α-induced necroptosis signaling, which strengthens our findings that ROS plays a critical role in activation of TLR4 and necroptosis induced by HG in H9c2 cardiac cells. Next, our further studies revealed that NAC or TAK-242 or Nec-1 respectively attenuated the HG-induced cardiac injuries and inflammation, as indicated by an increase in cell viability, and a decrease in ROS generation, dissipation of MMP and the secretion levels of IL-1β as well as TNF-α.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Taken together, our results clearly demonstrated that there is a link among ROS, TLR4 and RIP3, and that ROS mediates the HG-induced activation of TLR4 and necroptosis. Schenk et al [31] more recently showed that ROS regulate Smac mimetic/TNF-α-induced necroptosis signaling, which strengthens our findings that ROS plays a critical role in activation of TLR4 and necroptosis induced by HG in H9c2 cardiac cells. Next, our further studies revealed that NAC or TAK-242 or Nec-1 respectively attenuated the HG-induced cardiac injuries and inflammation, as indicated by an increase in cell viability, and a decrease in ROS generation, dissipation of MMP and the secretion levels of IL-1β as well as TNF-α.…”
Section: Discussionsupporting
confidence: 79%
“…Increasing evidence indicates that necroptosis is activated by several pathways, such as tumor necrosis factor-α (TNF-α) [26, 27], TLRs [28, 29] and ROS [21, 30]. Since HG has been shown to induce ROS generation, TNF-α and TLR4 expression as well as necroptosis, and there is a link between ROS, TNF-α and necroptosis in human FADD-deficient Jurkat cells [31], thus we speculated that ROS-TLR4-necroptosis pathway may be an important intracellular signaling mechanism which contributed to the HG-induced cardiac injury and inflammation. Furthermore, we explored whether the inhibition of this pathway contributes to the protective effect of K ATP channels against the HG-induced injury and inflammation in H9c2 cardiac cells.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that, in FADD-deficient acute lymphoblastic leukemia cells, ROS induction is a critical regulator of necroptotic cell death induced by a Smac mimetic in combination with TNF␣. Consistent with the definition of necroptosis, this cell death is caspase-independent (46,47). In contrast, ROS-mediated cell death induced by sorafenib/ TRAIL is blocked by the caspase inhibitor Q-VD-OPh, indicating induction of apoptotic cell death.…”
Section: Discussionmentioning
confidence: 55%
“…13,14 The relevance of the former is unclear because cardiolipin is believed to be exclusively mitochondrially localized, yet mitochondria and the PGAM5-Drp1 mitochondrial fragmentation pathway are not universally required for necroptosis. 5,20,[26][27][28] Here, we observed that the 4HB domains of mouse and frog MLKL, which kill MDFs, and human and chicken 4HB domains, which do not, could permeabilize membranes and exhibited a clear preference for plasma membrane over mitochondrial composition liposomes. Unexpectedly, full-length human, frog and chicken MLKL were more potent and rapid inducers of membrane permeabilization than the recombinant NTDs alone, suggesting a function for the pseudokinase domain in augmenting 4HB domain-mediated membrane permeabilization.…”
Section: Discussionmentioning
confidence: 82%